2023
DOI: 10.3390/biomedicines11082151
|View full text |Cite
|
Sign up to set email alerts
|

Demographic and Clinical Predictors of Drug Response in Epileptic Children in Jeddah

Rania Magadmi,
Reem Alyoubi

Abstract: Epilepsy is a chronic neurological disease of the brain. Over 20 antiseizure medications are available on the market, but a third of patients still have drug-resistant epilepsy. This study was designed to assess the impact of the demographic and clinical characteristics of epileptic children on their likelihood of developing drug resistance. This study was a multicenter, hospital-based, cross-sectional, case–control study of pediatric patients diagnosed with epilepsy in Jeddah, Saudi Arabia. The study included… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Our review included 13 articles covering 3801 people with epilepsy (PWE). Only four studies were retrospective [ 11 , 21 - 23 ] and nine were cross-sectional [ 17 , 24 - 31 ].…”
Section: Reviewmentioning
confidence: 99%
See 4 more Smart Citations
“…Our review included 13 articles covering 3801 people with epilepsy (PWE). Only four studies were retrospective [ 11 , 21 - 23 ] and nine were cross-sectional [ 17 , 24 - 31 ].…”
Section: Reviewmentioning
confidence: 99%
“…All studies assessed the general characteristics of patients with epilepsy. As for the patient's age, it ranged from 0 to 90 years and 8 studies showed a male predominance [ 11 , 17 , 21 , 22 , 25 , 26 , 28 , 31 ]. According to the family history of epilepsy, it was seen only in five studies [ 17 , 22 , 24 , 25 , 30 ] and showed a prevalence ranging from 6% to 24.9% [ 22 , 30 ].…”
Section: Reviewmentioning
confidence: 99%
See 3 more Smart Citations